Akkermansia deficiency and mucin depletion are implicated in intestinal barrier dysfunction as earlier event in the development of inflammation in interleukin-10-deficient mice - López-Cauce, Beatriz; Puerto, Marta; García, Juan José; Ponce-Alonso, Manuel; Becerra-Aparicio, Federico; del Campo, Rosa; Peligros, Isabel; Fernández-Aceñero, María J.; Gómez-Navarro, Yésica; Lara, José M.; Miranda-Bautista, José; Marín-Jiménez, Ignacio; et al. (Frontiers in Microbiology, 2023)
Background: Dysbiosis and mucin depletion are related with intestinal barrier dysfunction and seems to be an early pathophysiological event in inflammatory bowel disease (IBD). The objective of this work is to study these parameters in the natural history of colitis in IL-10 deficient mice (KO). Methods: Wild type (WT) and KO mice were followed until sacrifice at 3, 5, 10, 20, 57 and 70 weeks. Body weight, colonic weight/length ratio and in vivo intestinal permeability were registered. Expression of inflammatory and adhesion molecules in the colon was explored by qPCR as mucin-2 (MUC-2) and molecules involved in goblet cell maturation IL-18 and WAP Four-Disulfide Core Domain 2 (WFDC2), the endoplasmic reticulum stress markers X-box-binding protein (Xbp-1) and Reticulon-4B (RTN-4B). Bacterial composition in feces and colonic mucosa was determined by massive sequencing of the V3-V4 regions of 16S rDNA gene. Results: KO mice showed histological inflammation at weeks 20 and 57, but most notably the intestinal permeability was significantly higher from week 10. Concordantly, the number of goblet cells and expression of MUC-2, IL-18, WFDC2 and XBP-1 were significantly lower in KO from week 10. Nevertheless, no significant differences were found in the mRNA expression of MUC-2 or Xbp-1 between both groups – derived colon organoids. Significant bacterial differences began at week 5, being the Akkermansia deficiency in KO the most relevant result. Conclusion: Gut microbiota alterations and mucin depletion are associated with early intestinal barrier dysfunction and precede overt gut inflammation in this animal model of IBD.